Human endothelial progenitor cells rescue cortical neurons from oxygen-glucose deprivation induced death. (19th September 2016) - Bacigaluppi, Susanna; Donzelli, Elisabetta; De Cristofaro, Valentina; Bragazzi, Nicola Luigi; D'Amico, Giovanna; Scuteri, Arianna; Tredici, Giovanni
Highlights: Neuronal ischemia was studied in vitro with OGD on a primary rat embryonic cortical neuron culture. At day 2, after 2 hrs OGD, neuronal survival without treatment was impaired. At day 2, after 2 hrs OGD, treatment with indirect co-cultures with hEPC or hMSC significantly increased neuronal survival. Conditioned medium by hEPC or hMSC did not provide any advantage in terms of survival to OGD neurons. Abstract: Background and aim: Cerebral ischemia is characterized by both acute and delayed neuronal injuries. Neuro-protection is a major issue that should be properly addressed from a pharmacological point of view, and cell-based treatment approaches are of interest due to their potential pleiotropic effects. Endothelial progenitor cells have the advantage of being mobilized from the bone marrow into the circulation, but have been less studied than other stem cells, such as mesenchymal stem cells. Therefore, the comparison between human endothelial progenitor cells (hEPC) and human mesenchymal progenitor cells (hMSC) in terms of efficacy in rescuing neurons from cell death after transitory ischemia is the aim of the current study, in the effort to address further directions. Materials and methods: In vitro model of oxygen-glucose deprivation (OGD) on a primary culture of rodent cortical neurons was set up with different durations of exposure: 1, 2 and 3 hrs with assessment of neuron survival. The 2 hrs OGD was chosen for the subsequent experiments. After 2 hrs OGD neurons were either placed in indirect co-culture with hMSC or hEPC or cultured in hMSC or hEPC conditioned medium and cell viability was evaluated by MTT assay. Results: At day 2 after 2 hrs OGD exposure, mean neuronal survival was 47.9 ± 24.2%. In contrast, after treatment with hEPC and hMSC indirect co-culture was 74.1 ± 27.3%; and 69.4 ± 18.8%, respectively. In contrast, treatment with conditioned medium did not provide any advantage in terms of survival to OGD neurons Conclusion: The study shows the efficacy of hEPC in indirect co-culture to rescue neurons from cell death after OGD, comparable to that of hMSC. hEPC deserve further studies given their potential interest for ischemia.